2018
DOI: 10.1016/j.jcin.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Low Coronary Wall Shear Stress Is Associated With Severe Endothelial Dysfunction in Patients With Nonobstructive Coronary Artery Disease

Abstract: Objectives: We investigated the relationship between low wall shear stress (WSS) and severe endothelial dysfunction (EDFx). Background: Local hemodynamic forces, such as WSS play an important role in atherogenesis through their effect on endothelial cells. We hypothesized that low WSS independently predicts severe EDFx in patients with coronary artery disease (CAD). Methods: Forty-four patients with CAD underwent coronary angiography, fractional flow reserve (FFR) and endothelial function testing. Segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…Newtonian and non-Newtonian blood models are also compared in Thanapong Chaicana et al, [12] paper, where there are almost similar values for WSS in both blood models, representing huge similarities in WSS values although having different blood models. Based on the [11,12,8,18,19,21] papers, we can find a mutual agreement of the authors regarding hemodynamic parameters related significantly to the physiological blood flow. Details of the studies can be observed in Table 1 and Table 2.…”
Section: Principle Outcome: Comparison Of Methods Equations and Finmentioning
confidence: 74%
See 3 more Smart Citations
“…Newtonian and non-Newtonian blood models are also compared in Thanapong Chaicana et al, [12] paper, where there are almost similar values for WSS in both blood models, representing huge similarities in WSS values although having different blood models. Based on the [11,12,8,18,19,21] papers, we can find a mutual agreement of the authors regarding hemodynamic parameters related significantly to the physiological blood flow. Details of the studies can be observed in Table 1 and Table 2.…”
Section: Principle Outcome: Comparison Of Methods Equations and Finmentioning
confidence: 74%
“…CFD is a tool that has been used for decades in simulation and fluid flow processes. Many researchers consider this method while underwent experimental and simulation investigation for their research as it is time-consuming and low in cost [8,11,12,[18][19][20]. This CFD method not only limited to the selective field such as the mechanical and fluid field but also brings a great contribution to medical fields.…”
Section: Methodology 21 Data Extraction and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…increasing evidence has demonstrated that the endothelial dysfunction process is directly influenced by various factors, including nitric oxide dysfunction, epigenetic factors, oxidative stress, inflammatory factors and low shear stress (LSS) (5)(6)(7)(8)(9)(10)(11). among these, lSS, tangential stress produced by endothelial surface blood flow friction, which is observed at bifurcations, branching points and inside areas of curved segments of the coronary artery, induces inflammation and apoptosis, and subsequently disrupts the endothelial barrier, eventually leading to atherosclerosis (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%